Islam, Big Data, and Digital Ethics: Challenges in Religious Life in the Digital Age - Agung Saputra; Erni Asneli Asbi (Pharos Journal of Theology)
Advances in artificial intelligence (AI) and big data have transformed various aspects of life, including the religious dimension, with significant impacts on Islamic religious practices. These technologies offer opportunities to enhance the efficiency of religious practices, such as prayer reminders, Quran recitation, and zakat distribution, but they also present ethical challenges related to privacy, data misuse, and the erosion of deep spiritual experiences. This article examines the impact of AI and big data on Islamic spirituality, highlighting fundamental Islamic principles such as justice, honesty, and kindness. While these technologies can enhance efficiency, their use may also diminish the quality of the deeply personal experience of faith. To address these challenges, this article proposes recommendations to align technological advancements with Islamic values, with the aim of enriching spiritual practices without compromising the core teachings of the religion. These recommendations emphasise the importance of a proactive Islamic digital ethics framework to mitigate risks and ensure responsible innovation in the use of these technologies.